Does dollarization mean importing the Fed's monetary policy? - Steven Kamin; Paul Carrillo-Maldonado; Benedict J. Clements; Aatman Vakil (American Enterprise Institute (AEI), 2024)
The electoral campaign of Argentina's new president Javier Milei has revived the debate over the pros and cons of dollarization. Critics argue that dollarizing would force Argentina to import the monetary policy of the Federal Reserve, regardless of whether the Fed's policies are appropriate for it. But because of the centrality of the dollar in the global economy, U.S. monetary policies tend to spill over to foreign economies, whether or not they have their own currency. In this paper, we address this issue empirically by comparing the response to changes in U.S. interest rates of domestic deposit and loan rates in three Latin American dollarized economies (Ecuador, El Salvador, and Panama) and three non-dollarized economies (Chile, Colombia, and Mexico). We find, first, that domestic bank interest rates are not perfectly responsive to U.S. interest rates, even in dollarized economies; this may reflect barriers to capital flows, domestic controls, and/or uncompetitive banking markets. Second, deposit interest rates do appear to be somewhat more linked to U.S. interest rates in dollarized economies than in non-dollarized economies. Third, however, bank loan rates are at least as responsive to U.S. interest rates in non-dollarized economies as in dollarized ones. All told, we do not find stark differences between dollarized and non-dollarized economies in the response of domestic bank interest rates to U.S. rates. This suggests fears of importing U.S. monetary policy should not be a primary consideration as policymakers decide whether or not to dollarize their economy.
Keywords: 330; Argentina; Federal Reserve; International economy; Monetary policy; US dollar